Kebijakan Sekolah Dalam Mengatasi Kesulitan Belajar Pada Siswa Di SDI Bimoku Kota Kupang - Romanus Bagas Rian; Jordi Selan; Misraim Riwu (Lembag, 2024)
This research aims to understand the school's policies in addressing learning difficulties of students at SDI Bimoku. This qualitative research uses a case study approach, with subjects being students experiencing learning difficulties and the object of study being the school's policies in addressing these difficulties. The principal and class teachers, who handle the students directly, are the primary sources of data obtained through interviews and observations at SDI Bimoku in Kupang City. Secondary data sources are gathered from books, the internet, and other documents. Data analysis in this study follows the Miles & Huberman method, which includes data reduction, data presentation, and conclusion drawing. The validity of the data is tested using the triangulation technique. The results show that learning difficulties at SDI Bimoku include both academic and non-academic challenges. The causes of these difficulties are internal and external factors. The school's policies to address student learning difficulties include initial tests, teacher observation during the learning process, remedial programs, and curriculum adjustments. These policies, implemented through various school programs, largely meet the school's expected outcomes, though some students require special and longer-term attention due to persistent learning difficulties. However, based on the obtained information, the school's programs have improved the grades of several students who previously had learning difficulties. Overall, it can be concluded that the school's policies through these programs are considered successful.